Changes in mean and extreme rainfall indices over a problemscape in central Ethiopia - Bewket, Woldeamlak; Tibebe, Degefie; Teferi, Ermias; Degefu, Mekonnen Adnew (Elsevier, 2024)
Daily gridded rainfall dataset with 0.04° spatial resolution, which is gauge-satellite merged product, for the period 1983–2018 was used to evaluate changes in the spatiotemporal behavior of rainfall amount, precipitation concentration index (PCI) and extreme event indices over central Ethiopia that shares common water system challenges, and thus referred to as a problemscape. Twelve of the precipitation-related indices developed by the Expert Team on Climate Change Detection and Indices (ETCCDI) were used. The results show that rainfall displays complex spatial variability, and mean and extreme rainfall indices indicate a mix of increasing and decreasing changes for the different indices and parts of the problemscape. A major conclusion from the findings is that the spatial variability of rainfall is highly complex, and hence a high resolution monitoring and analysis is important to monitor local scale manifestations of climate change and design locally-relevant adaptation interventions. The study provides useful insights for adaptation planning and decision making in water, agriculture and other sectors in the study area.